Is insulin resistance a predictor for complete response in breast cancer patients who underwent neoadjuvant treatment? - DANE, FAYSAL; KAYA, HANDAN; UĞURLU, MUSTAFA ÜMİT; DEMİRCAN, NAZIM CAN; YUMUK, PERRAN FULDEN; ARIKAN, RUKİYE; BAŞOĞLU TÜYLÜ, TUĞBA; AKIN TELLİ, TUĞBA (BMC, 2020)
Purpose Neoadjuvant chemotherapy is the standard front-line treatment modality in locally advanced breast cancer. Achieving pathological complete response (pCR) is a significant prognostic factor for prolonged disease-free and overall survival. Insulin resistance is defined as a pathological condition in which insulin effect is impaired in peripheral target tissues such as the skeletal muscle, liver, and adipose tissue. The relationship between breast cancer and insulin resistance is controversial. In this study, our aim is to evaluate the role of insulin resistance, body mass index (BMI), metabolic syndrome, and inflammation markers to predict complete response in breast cancer patients who underwent neoadjuvant treatment. Methods Data from 55 locally advanced non-diabetic breast cancer patients, treated with neoadjuvant chemotherapy between 2015 and 2017, were retrospectively evaluated. Homeostatic model assessment, IR = insulin resistance (HOMA-IR) was calculated by using the obtained insulin and fasting blood glucose values before neoadjuvant chemotherapy (fasting insulin x fasting glucose/405). We considered a cut-off of 2.5 for insulin resistance. The systemic inflammatory index (SII), neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) were calculated. Results Twenty-five patients had no insulin resistance. The most common pathologic subtype (56%) was hormone receptor (HR) positive and human epidermal growth factor receptor-2 (Her-2)-negative invasive ductal carcinoma. Sixteen (29%) patients had a pathological complete response (pCR). We found that the probability of pCR in patients with insulin resistance was 4.7 times lower than that in patients without insulin resistance [OR: 4.7 (95%CI 1.7-17.2),p= 0.01]. Conclusion Our results revealed that insulin resistance may have a negative effect on pathological complete response (pCR) following neoadjuvant therapy particularly with hormone-positive and Her-2-negative cases of non-diabetic breast cancer.
Keywords: Breast cancer; Neoadjuvant treatment; Insulin resistance; HOMA-IR; Inflammation-based indices; Pathological complete response; GROWTH-FACTOR-I; NECROSIS-FACTOR-ALPHA; BINDING PROTEIN-3; DIABETIC-PATIENTS; RISK; CHEMOTHERAPY; INFLAMMATION; EXPRESSION; METFORMIN; MORTALITY